The Influence Of Knowledge Management On Organizational Innovation Of Community Technical Implementation Units In Sijunjung And Sawahlunto Discipities - Putri Amelia; Kusmiyanti Kusmiyanti (Dinasti Publisher, 2024)
Management knowledge is matter important related with context innovation in organization , especially in the Technical Implementation Unit , especially in the Regency Sijunjung and Sawahlunto which require constant adaptation and change . Formulation problem in study This is whether There is influence management knowledge to innovation organization of implementation units technical correctional facilities in the district Sijunjung and Sawahlunto ? This study aiming For give Contribution positive from study in understand How Management Knowledge to Innovation Correctional UPT Organization in the Regency Sijunjung and Sawahlunto , and provide alternative solution with give attention to justice organization use increase innovation in organization . Research methods This use study quantitative with non- probability sampling technique as many as 120 employees . Data collection techniques can be done use questionnaires distributed via google form. There are 22 questions that have gone through the measurement model test (outer model) and the structural model test (inner model) which were processed use SmartPLS SEM software assistance version 4. Research results show mark significant through the Path Coefficient ( Direct Effect) test of 0.000 <0.05, so that H0 and Ha are accepted which exist influence management knowledge to innovation organization . The results of the coefficient test Determination obtained The R Square value is 0.812, which indicates variable management knowledge give influence by 81.2% against innovation organization whereas the rest 18.8 % influenced other variables that are not explained in study This . From the results study This can drawn the conclusion that there is positive and significant relationship between management knowledge to innovation organization of Correctional Technical Implementation Unit in the Regency Sijunjung and Sawahlunto